Prediksi Masa Studi Mahasiswa Menggunakan Metode Topsis Pada Program Studi Ilmu Komputer Universitas Nusa Cendana - Emerensye Sofia Yublina Pandie; Rheza A Costa; Nelci Dessy Rumlaklak (J-Icon : Jurnal Komputer dan Informatika, 2020)
Graduation rates are considered as one of the parameters of the effectiveness of educational institutions. The period of student studies is an important issue that needs to be handled wisely by the Undana Computer Science department. Because graduation rates on time and not on time will affect the accreditation of majors, so we need a solution to be able to improve the problem of graduation on time. The solution that can help supervise and pay attention to active students in the 5th semester in order to graduate on time is to use a Decision Support System. Decision Support System can help predict the period of study of students with the TOPSIS method. The criteria used are Gender, Number of SKS that have been taken, Semester GPA, Cumulative Achievement Index and subsequent SKS Load. Sensitivity testing is done by adding a weight value of 0.5 and 1 to each criterion to get the results of criteria that are sensitive to changes in weights namely the GPA criterion of 3.92% change and subsequent SKS Load criteria of 3.92% change. The results of testing the sensitivity of criteria weights have an average percentage change in yield of 0.78%.